Non-absorbable disaccharides for hepatic encephalopathy: systematic review of randomised trials - Als-Nielsen, Bodil (BMJ Publishing Group Ltd., 2004)
Objective To assess the effects of non-absorbable disaccharides (lactulose and lactitol) in patients with hepatic encephalopathy. Data sources Cochrane Hepato-Biliary Group controlled trials register, Cochrane Library, Medline, and Embase until March 2003; reference lists of relevant articles; authors and pharmaceutical companies. Review methods Randomised trials that compared non-absorbable disaccharides with placebo, no intervention, or antibiotics for hepatic encephalopathy were included. The primary outcome measures were no improvement of hepatic encephalopathy and all cause mortality. Results 22 trials were included. Compared with placebo or no intervention, non-absorbable disaccharides seemed to reduce the risk of no improvement in patients with hepatic encephalopathy (relative risk 0.62, 95% confidence interval 0.46 to 0.84, six trials). However, high quality trials found no significant effect (0.92, 0.42 to 2.04, two trials). Compared with placebo or no intervention, non-absorbable disaccharides had no significant effect on mortality (0.41, 0.02 to 8.68, four trials). Non-absorbable disaccharides were inferior to antibiotics in reducing the risk of no improvement (1.24, 1.02 to 1.50, 10 trials) and lowering blood ammonia concentration (weighted mean difference 2.35 μmol/l, 0.06 μmol/l to 13.45 μmol/l, 10 trials). There was no significant difference in mortality (0.90, 0.48 to 1.67, five trials). Conclusions There is insufficient evidence to support or refute the use of non-absorbable disaccharides for hepatic encephalopathy. Antibiotics were superior to non-absorbable disaccharides in improving hepatic encephalopathy, but it is unclear whether this difference is clinically important. Non-absorbable disaccharides should not serve as comparator in randomised trials on hepatic encephalopathy.